Optimization on Preparation Conditions of Salidroside Liposome and Its Immunological Activity on PCV-2 in Mice. (23rd March 2015) - Feng, Yibo; Zhao, Xiaojuan; Lv, Fang; Zhang, Jinqiu; Deng, Bihua; Zhao, Yanhong; Hu, Yuanliang; Wang, Deyun; Liu, Jiaguo; Lu, Yu; Bo, Ruonan; Liu, Zhenguang
Abstract : The aim of this study was to optimize the preparation conditions of salidroside liposome with high encapsulation efficiency (EE) and to study the immunological enhancement activity of salidroside liposome as porcine circovirus type 2 virus (PCV-2) vaccine adjuvant. Response surface methodology (RSM) was selected to optimize the conditions for the preparation of salidroside liposome using Design-Expert V8.0.6 software. Three kinds of salidroside liposome adjuvants were prepared to study their adjuvant activity. BALB/c mice were immunized with PCV-2 encapsulated in different kinds of salidroside liposome adjuvants. The PCV-2-specific IgG in immunized mice serum was determined with ELISA. The results showed that when the concentration of ammonium sulfate was 0.26 mol· L −1, ethanol volume 6.5 mL, temperature 43°C, ethanol injection rate 3 mL· min −1, and salidroside liposome could be prepared with high encapsulation efficiency of 94.527%. Salidroside liposome as adjuvant could rapidly induce the production of PCV-2-specific IgG and salidroside liposome I adjuvant proved to provide the best effect among the three kinds of salidroside liposome adjuvants.